Enhancing fiber/matrix bonding in polypropylene fiber reinforced cementitious composites by microbially induced calcite precipitation pre-treatment - Hao, Yifei; Cheng, Liang; Hao, Hong; Shahin, Mohamed (Elsevier, 2018)
In fiber reinforced cementitious composites (FRCC), bonding between the fibers and matrix governs many important properties, including strengths, fracture energy, ductility, and energy absorption capacities. This study explores the application of a microbiological process of microbially induced calcite precipitation (MICP) to pre-treating surface of polypropylene (PP) fibers for enhancing the interfacial boning strength. This technique utilizes MICP process to produce calcium carbonate that binds onto the fiber surface, leading to increased interfacial bond area and strength. Laboratory tests indicate that MICP modification could increase the post-cracking resistance and energy absorption capacity of the FRCC beam specimens by 58% and 69.3%, respectively. Microstructure analysis reveals that PP fibers after MICP treatment were coated with a layer of CaCO3 with thickness around 20–50 μm depending on the degree of deposition. Results acknowledged a significant role of MICP pre-treatment in enhancing the fiber-matrix bonding properties of FRCC and the corresponding mechanical performance.